Multicentre study of short‐course radiotherapy and transanal endoscopic microsurgery for early rectal cancer. Issue 8 (5th May 2016) - Smart, C. J.; Korsgen, S.; Hill, J.; Speake, D.; Levy, B.; Steward, M.; Geh, J. I.; Robinson, J.; Sebag‐Montefiore, D.; Bach, S. P.
Abstract: Background: Organ‐preserving treatment for early‐stage rectal cancer may avoid the substantial perioperative morbidity and functional sequelae associated with total mesorectal excision (TME). The initial results of an organ‐preserving approach using preoperative short‐course radiotherapy (SCRT) and transanal endoscopic microsurgery (TEMS) are presented. Methods: Patients with cT1–2N0 rectal cancers staged using high‐quality MRI and endorectal ultrasonography received SCRT, with TEMS 8–10 weeks later, at four regional referral centres between 2007 and 2013. Patients were generally considered high risk for TME surgery (a small number refused TME). Results: Following SCRT and TEMS, 60 (97 per cent) of 62 patients had an R0 resection. Histopathological staging identified 20 ypT0 tumours, 23 ypT1, 18 ypT2 and one ypT3. Preoperative uT category was significantly associated with a complete pathological response, which was achieved in 13 of 27 patients with uT0/uT1 disease and in five of 29 with uT2 ( P = 0·010). Acute complications affected 19 patients, the majority following TEMS. No fistulas occurred and no stomas were formed. Surveillance detected four intraluminal local recurrences at a median follow‐up of 13 months, all in patients with tumours staged as ypT2. Salvage TME achieved R0 resection in three patients and a stent was placed in one patient owing to co‐morbidities. Conclusion: SCRT with TEMS was effective in the majority of patients considered high risk for (or who refused) TME surgery. Abstract : A very attractive option